Adipose-Derived Circulating Exosomes Promote Protection of the Pulmonary Endothelial Barrier by Inhibiting EndMT and Oxidative Stress through Down-Regulation of the TGF-β Pathway: A Potential Explanation for the Obesity Paradox in ARDS. (5th May 2022) - Qi, Di; Deng, Wang; Chen, Xiaorui; Fan, Shulei; Peng, Junnan; Tang, Xumao; Wang, Daoxin; Yu, Qian
Abstract : The "obesity paradox in acute respiratory distress syndrome" (ARDS) refers to the phenomenon in which obesity is associated with higher morbidity but lower mortality in patients with ARDS. Endothelial-to-mesenchymal transition (EndMT) represents a key link in the interaction between endothelial disruption and mesenchymal fibrosis under inflammatory and oxidative conditions, which represent the intersectional pathophysiology of ARDS. Adipose tissue is considered to constitute the major source of circulating exosomal microRNAs (miRNAs), which act as genetic forms of adipokines for cell–cell crosstalk. We aimed to demonstrate the regulation and mechanism of adipose-derived exosomes in the obesity paradox in ARDS. High-fat-induced obese mice and lean control mice were subjected to ARDS insult to investigate the effects of obesity on ARDS and microarray analysis was performed to screen for differences in circulating miRNAs. In addition, mice and pulmonary endothelial cells were administered with adipose-derived exosomal miR-122-5p to investigate the underlying molecular mechanisms. We found high-fat diet-induced obesity protected against ARDS in mice by reinforcing endothelial barrier and attenuating fibroproliferation. Circulating exosomes produced in the obese state mediated these protective effects by inhibiting EndMT and oxidative stress. Mechanistically, adipose-derived exosomal miR-122-5p promoted the integrity and function of pulmonary endothelial barrier and alleviated fibrogenesis by suppressing EndMT and oxidative stress through down-regulation of the transforming growth factor β 1 (TGF- β 1)/TGF- β receptor 1 (TGF- β R1)/Smad2 pathway in vivo and in vitro. In conclusion, adipose-derived circulating exosomal miR-122-5p protects against ARDS by reinforcing pulmonary endothelial barrier through inhibition of EndMT and oxidative stress via down-regulation of the TGF- β pathway, which propose a potential explanation for the obesity paradox in ARDS and indicate promising prospects for adipose-derived exosomes in cell-free therapies for ARDS.